SISTEM PERADILAN JURY (Analisis Ke-Islam-an dan Penerapan di Indonesia) - Ngimadudin Ngimadudin (El-Ghiroh : Jurnal Studi Keislaman, 2016)
Legal empowerment towards substantive justice will always experience the discourse of its own in seeking legal problematics as chief justice. Indonesian state has its own characteristics in all-an heterogeneous social certainly have its own problems in determining the appropriate legal format and is able to achieve the ideals of the universality of the law itself. In the perspective of the history of the formation of Indonesian legal system is inseparable from the development of indigenous intensity, Islam, and Europe as a nation invaders that affect the formation of (mostly) legal order in Indonesia. Tangled laws that have not been on a portion of substantive justice certainly needs serious handling to determine the exact formulation, so that the development of society that is fast enough it can also be offset by the acceleration of the legal order that can address the development of the social order. The search process may be started from the concept of legal materials, legal policy makers and the legal process itself. Adopting the grand jury system would at least give a new color in the constellation of the legal process that occurred in Indonesia. The changing pattern of the law will have a significant impact on the way people simply on the substantive legal justice. Although on the other hand the majority of the people of Indonesia (Islam) ask about this grand jury system.